2023
DOI: 10.3389/fimmu.2022.1093607
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes as smart drug delivery vehicles for cancer immunotherapy

Abstract: Exosomes (Exos) as drug delivery vehicles have been widely used for cancer immunotherapy owing to their good biocompatibility, low toxicity, and low immunogenicity. Some Exos-based cancer immunotherapy strategies such as tuning of immunosuppressive tumor microenvironment, immune checkpoint blockades, and cancer vaccines have also been investigated in recent years, which all showed excellent therapeutic effects for malignant tumor. Furthermore, some Exos-based drug delivery systems (DDSs) for cancer immunothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 197 publications
(242 reference statements)
0
19
0
Order By: Relevance
“…The optimal hydrogel H1 was used for its superior biocompatibility and rheological properties to demonstrate the ability to carry and release therapeutics agents. Exosomes have been widely used in the treatment of various diseases due to their excellent biocompatibility, low toxicity, and low immunogenicity (63). In this study, Mens-exo was used as a model drug that demonstrated the potential of the optimal hydrogel for therapeutic agents delivery.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal hydrogel H1 was used for its superior biocompatibility and rheological properties to demonstrate the ability to carry and release therapeutics agents. Exosomes have been widely used in the treatment of various diseases due to their excellent biocompatibility, low toxicity, and low immunogenicity (63). In this study, Mens-exo was used as a model drug that demonstrated the potential of the optimal hydrogel for therapeutic agents delivery.…”
Section: Discussionmentioning
confidence: 99%
“…37 The TME is important for tumor proliferation, invasion and metastasis, as well as influencing treatment outcome. 38 It depends on the tumor cell collusion with its surrounding environment. 39 The microenvironment around the tumor includes innate and adaptive immune cells, which express a variety of cytokines that interact with cancer cells.…”
Section: Tumor Immune Escapementioning
confidence: 99%
“…[71] This is especially relevant for immunotherapy, where the precise delivery of therapeutic agents to specific cells is critical. [72,73] One of the key advantages of this delivery technique is its specificity. EVs can be engineered to carry specific immunotherapeutic agents and to target specific cells, [74] reducing off-target effects and improving the efficacy of the therapy (see Figure 1C).…”
Section: M3: Ev-based Membrane Fusionmentioning
confidence: 99%